Media Magic Box: Optimization of the Ability to Recognize Letters in Early Children - Novalina, Eva; Syafril, Syafrimen; Nopriansyah, Untung (Universitas Islam Negeri Raden Intan Lampung, 2023)
The phenomenon of improving the ability to recognize letters in early childhood in schools has been implemented well, but the learning media is less varied in learning to introduce letters. This research method uses classroom action research (PTK) using the Kemmis and MC Taggart models. The research involved 1 experienced teacher and 12 students. To see the development of the ability to recognize letters in young children, data was collected using in-depth observations of the learning process carried out by the teacher in 8 meetings in 2 cycles, with a duration of 90 minutes for each observation (during the learning process). Data collection techniques were carried out using observations with students in RA at-taqwa group B, totaling 12 children, interviews with 1 class teacher and documentation. The research results show that the ability to recognize letters in early childhood generally develops very well (BSB) through magic box media. This development can be seen gradually in cycle I and cycle II (16.6% in cycle I and 83.3% in cycle II). The development of the ability to recognize letters in early childhood in this study is assumed to be successful because it has reached a success standard of above 75%. So this game has an important role in the development of language, cognitive, physical motor skills, religious and moral values and social emotional development.